Rhodium Catalyst Structural Changes during, and Their Impacts on the Kinetics of, CO Oxidation - Marino, Silvia; Wei, Lai; Cortés-Reyes, Marina; Cheng, Yisun; Laing, Paul; Cavataio, Giovanni; Paolucci, Christopher; Epling, William (ACS Publications, 2023)
Catalysts can undergo structural changes during the reaction, affecting the number and/or the shape of active sites. For example, Rh can undergo interconversion between nanoparticles and single atoms when CO is present in the reaction mixture. Therefore, calculating a turnover frequency in such cases can be challenging as the number of active sites can change depending on the reaction conditions. Here, we use CO oxidation kinetics to track Rh structural changes occurring during the reaction. The apparent activation energy, considering the nanoparticles as the active sites, was constant in different temperature regimes. However, in a stoichiometric excess of O2, there were observed changes in the pre-exponential factor, which we link to changes in the number of active Rh sites. An excess of O2 enhanced CO-induced Rh nanoparticle disintegration into single atoms, affecting catalyst activity. The temperature at which these structural changes occur depend on Rh particle size, with small particle sizes disintegrating at higher temperature, relative to the temperature required to break apart bigger particles. Rh structural changes were also observed during in situ infrared spectroscopic studies. Combining CO oxidation kinetics and spectroscopic studies allowed us to calculate the turnover frequency before and after nanoparticle redispersion into single atoms.
Keywords: Catalizadores; Eliminación de contaminantes